Hal-Hal Yang Ada Hubungan Dengan Diabetes Melitus Tipe II Pada Penderita Di Beberapa Lokasi Di Wilayah Eropa Periode Tahun 2012 Sampai Dengan Tahun 2021 - Azzhara, Nurul Fakhira; Rompegading, Andi Machmud; Sartika, Suriana Dwi (Fakultas Kedokteran Universitas Bosowa, 2024)
Type 2 diabetes is a type of diabetes that is generally caused by insulin resistance and decreased pancreatic beta cell function, where insulin resistance causes the body to not fully respond to insulin. The purpose of this study was to find out things that have a relationship with the occurrence of type II diabetes mellitus in several locations in the Asia-Africa region from 2012 to 2021. The research method is an analytical research by synthesizing the results obtained by nine scientific research articles with a case control research design. The results of the eleven studies analyzed show that there are things that have a relationship with the occurrence of type II diabetes mellitus in patients in several locations in the Europe region, which is a significant relationship between nutritional status, smoking habit, history of hypertension and family history. on the incidence of type II diabetes mellitus in several locations in the Asia-Africa region with p value < 0.05%. The Conclusion of the incidence of type II diabetes mellitus in several locations in the Europe region from 2012 to 2021 has a significant relationship to nutritional status, smoking habit, history of hypertension and family history.